Kinetic parameters of Candida tropicalis TISTR 5306 for ethanol production process using an optimal enzymatic digestion strategy of assorted grade longan solid waste powder - Saengkae Wattanapanom (2020)
© 2019, Chiang Mai University. All right reserved. The optimal enzymatic digestion strategy for assorted grade whole fruit longan solid waste powder (WF–LSWP) to release the highest level of fermentable sugars for subsequent production of ethanol using Candida tropicalis TISTR 5306 has been reported for the first time in this study with several important fermentation kinetic parameters. WF–LSWP contained relatively low lignin content (5.79 ± 0.43 %(w/w)) with the presence of relatively high starch and pectin contents of 27.9 ± 0.86% (w/w) and 2.07 ± 0.16% (w/w), respectively. Pretreatment by alkali and saturated steam before enzymatic digestion step did not result in the improvement of overall sugars being released. The implementation of commercial enzyme mixture (amylase, glucoamylase, cellulase, and xylanase) for one step enzymatic digestion at 50°C for 48 h resulted in the statistical significantly highest (p ≤ 0.05) specific overall sugars productivity of (141 ± 1.4) × 10–4 g total sugars/g WF–LSWP/digestion step/h. Cultivation of C. tropicalis TISTR 5306 in digested and concentrated WF–LSWP extract at concentration level of 90 g/l during 0 – 12 h resulted in the following statistical significantly highest (p ≤ 0.05) kinetic parameters; specific growth rate (m) of 0.097 ± 0.001 h–1 and specific ethanol production rate (qP) of 0.221 ± 0.010 gP/gX/h. Dried biomass yield (YX/S) and ethanol yield (YP/S) based on utilized sugars of 90 g/l WF–LSWP extract at 0.180 ± 0.018 gX/gS and 0.411 ± 0.044 gP/gS, respectively, were statistical significantly highest (p ≤ 0.05) in comparison with those of 16 and 45 g/l WF–LSWP extracts.